2022
DOI: 10.3390/jcm11030488
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on the Incidence and Characteristics of Patients with Psychiatric Illnesses Visiting Emergency Departments in Korea

Abstract: The global coronavirus disease 2019 (COVID-19) pandemic has had wide-ranging effects on the mental health of the public. This study aimed to investigate the impact of the COVID-19 pandemic on the characteristics of psychiatric patients who visited emergency departments (ED) during this time. A cross-sectional study was conducted including patients visiting 402 nationwide EDs from 27 January 2020 to 29 June 2020 (22 weeks; during-COVID) and the corresponding period in 2019 (28 January 2019 to 30 June 2019, 22 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…We observed that in both settings of UPCs the number of consultations per month differed from that of the previous year, showing a sort of relationship with the pandemic progress and its consequences on society. During the month of March 2020, in ER, we reported a drastic reduction of UPCs, which then increased in the following months, in line with most studies in different countries ( 30 36 , 48 ). The small number of consultations could be explained by the reduction of other ER activities to focus on pandemic needs and by decreased demand for UPC by the population due to the fear of contagion in hospital.…”
Section: Discussionsupporting
confidence: 89%
“…We observed that in both settings of UPCs the number of consultations per month differed from that of the previous year, showing a sort of relationship with the pandemic progress and its consequences on society. During the month of March 2020, in ER, we reported a drastic reduction of UPCs, which then increased in the following months, in line with most studies in different countries ( 30 36 , 48 ). The small number of consultations could be explained by the reduction of other ER activities to focus on pandemic needs and by decreased demand for UPC by the population due to the fear of contagion in hospital.…”
Section: Discussionsupporting
confidence: 89%
“…A higher burden of psychiatric diseases in youth during the COVID-19 pandemic has been suggested in a number of recent studies [9,[13][14][15]. In a cross-sectional online survey, the three most common psychiatric symptoms in primary and secondary school students during school closures due to COVID-19 outbreaks were anxiety, depression, and stress [13].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have linked globally stressful disasters to symptom deterioration and increased disease severity among patients with Crohn’s disease and ulcerative colitis [ 19 , 20 ]. The relevance of pandemic-related stress might be supported by the latest national and international demands for heightened attention to mental disorders and psychological distress during this pandemic [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%